The impossibility of an Esperanto linguistics / La neebleco de priesperanta lingvoscienco (InKoj. Philosophy & Artificial Languages, New series, 2011)
Abstract The task of linguistics is to reveal the principles which relate sen-tences to meanings. One cannot work out these principles if one does notknow (1) the grammatical sentences of the language and (2) their meanings. Due to absence of native speakers (the usual source of grammaticality and ofmeanings), sentence-meanings and grammaticality in Esperanto are radicallyimprecise in comparison with those of ethnic languages. Due to this impreci-sion it is not possible to construct linguistic arguments regarding Esperanto:esperantology is possible, but not a linguistics of Esperanto. The article examines in detail a concrete example of the kind of linguistic argument which is not possible in the case of our language. Any successful planned language, not only Esperanto, would present the same difﬁculties to linguistic science.The nature of crucial data and the somewhat famous declaration of Noam Chomsky that “Esperanto is not a language” are considered. Resumo La tasko de la lingvistiko estas malkovri la principojn, kiuj  kunligas frazojn kaj signifojn. Ne eblas ellabori tiujn principojn, se oni ne scias (1) la gramatikajn frazojn de la lingvo kaj (2) iliajn signifojn.  Pro manko de indiĝenaj parolantoj (la kutima datenfonto por  gramatikeco kaj por signifoj), frazosignifoj kaj gramatikeco en  Esperanto radikale malprecizas kompare kun la etnolingvoj. Pro tiu  malprecizo ne eblas konstrui lingvistikajn argumentojn pri  Esperanto: esperantologio eblas, sed ne  priesperanta lingvistiko. La artikolo detale ekzamenas konkretan  ekzemplon de la speco de lingvistika  argumento, kiu ne eblas en la kazo de nia lingvo. Iu ajn sukcesa  planlingvo, ne nur Esperanto,  prezentus al la lingvistiko la samajn malfacilaĵojn.   La naturo de krucaj decidaj datenoj kaj la iom  famiĝinta eldiro de Noam Chomsky, ke "Esperanto ne estas  lingvo", estas konsiderataj.